Can water rights trading pilot policy ensure food security in China? Based on the difference-in-differences method - Lan Fang; Yong Fu; Shaojian Chen; Hui Mao (Water Policy, 2021)
Ensuring food security in China is the primary task in solving the problems of 'agriculture, countryside, and farmers'. Based on Chinese provincial panel data from 2009 to 2018, this paper evaluates the impact of a water rights trading pilot policy (WRTPP) on food security and examines its underlying mechanism. To overcome the estimation bias existing in previous studies, we use the difference-in-differences method, which can separate time effects from policy treatment effects and is an effective tool to compare the effect before and after policy implementation. We, therefore, use this method to evaluate the net effect of the WRTPP on food security. It is found that the WRTPP can help ensure food security. This effect reaches its maximum in the fourth year after the policy's implementation. It is further found that the WRTPP can improve the adoption of agricultural water-saving irrigation technology to increase the grain yield. Our conclusions complement existing evidence on the factors influencing food security. From the perspective of improving farmers' water-saving irrigation technology, we confirm that the mechanism of the water rights trading pilot policy helps ensure food security.
Keywords: 330; difference-in-differences; food security; water rights trading pilot policy